2014
DOI: 10.1016/j.phpro.2014.10.057
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Magnetic Charging Chute to Improve Productivity of Sinter Machine at Rourkela Steel Plant

Abstract: Sintering is a process in sinter machine for agglomeration of iron ore and other raw material fines into a compact porous mass, i.e., sinter, used in Blast Furnaces as an iron bearing input charge material for hot metal production. 'Permeability' of sinter-bed on sinter machine i.e., the porosity in sinter-bed of charged materials, facilitates atmospheric air passes from the top to bottom across the depth of sinter-bed, when suction created from the bottom of the bed, for efficient heat carry over from top to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Honorato and Seshadri introduced an intensified sifting feeder (ISF) into the sintering process and demonstrated that it reduces the fractionation of coarse and fine particles, thereby enhancing permeability and increasing productivity [10]. Selvam et al introduced the Magnetic Charging Chute, incorporating magnetic force technology, to enhance the permeability of the feed material [11]. Kim et al developed three forms of charging chutes that can enhance the compaction of charging materials in the sintering process and analyzed them using DEM [6].…”
Section: Reinforcing Sinter Charging Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Honorato and Seshadri introduced an intensified sifting feeder (ISF) into the sintering process and demonstrated that it reduces the fractionation of coarse and fine particles, thereby enhancing permeability and increasing productivity [10]. Selvam et al introduced the Magnetic Charging Chute, incorporating magnetic force technology, to enhance the permeability of the feed material [11]. Kim et al developed three forms of charging chutes that can enhance the compaction of charging materials in the sintering process and analyzed them using DEM [6].…”
Section: Reinforcing Sinter Charging Segregationmentioning
confidence: 99%
“…Until recently, several chute designs have been proposed to enhance particle size segregation. These are the intensified sifting feeder (ISF), and magnetic braking feeder (MBF), which were reviewed in prior studies, and most chutes are based on the shape of a straight slope [10,11]. The existing straight slope can change the chute angle by adjusting the angle, but it is difficult to increase the trajectory segregation efficiency because the angles of the upper part where the mixed raw materials enter the chute and the lower part where they leave the chute are dependent on each other.…”
Section: Particle Behavior On a Cycloid Curvementioning
confidence: 99%